PETA BARU IDEOLOGI PARTAI POLITIK INDONESIA - Nurjaman, Asep (Jurnal Bestari, 2009)
Political parties, although they have been existed for periods of time, they do not still develop yet because there is no material-based social structure. Thus, when they came to reformation era, political parties still needed symbols as medium to lead people in structuring action system and ways in interpreting political reality so that it will be fit to the party's interest. I this context, ideology become very important in building relationship between party and the people. Therefore, dynamics and political affiliation which is more on party and people are still determined by both cultural equality and divergence in certain groups of people.